Monetary policy and bank stability: The analytical toolbox reviewed - Ugo Albertazzi; Francesca Barbiero; David Marqués Ibá\~nez; Alexander Popov; Costanza Rodriguez D'Acri; Thomas Vlassopoulos (European Central Bank (ECB), 2020)
The response of major central banks to the global financial crisis has revived the debate around the interactions between monetary policy (MP) and bank stability. This technical paper sheds light, quantitatively, on the different mechanisms underlying the relationship between MP and bank stability. It does so by reviewing microeconometric studies from the academic literature as well as those conducted internally at the ECB. The paper proceeds chronologically, using the recent crisis as a touchstone. First, it provides a brief overview of the main theoretical channels linking bank stability and the transmission of MP. It then analyses the evidence from the pre-crisis period in the light of the structural trends leading up to the crisis. As the crisis erupted, unconventional monetary policy (UMP) measures were deployed, and the paper suggests that these were essential to buttress bank stability and halt a systemic crisis. At the same time, these measures involved trade-offs, and the adverse spillovers on banks' intermediation capacity and risk-taking require close monitoring. The paper ends by offering a critical review of the methodologies employed and suggestions for the areas where analytical efforts should be focussed in the future.
Keywords: E4; E43; E5; E52; G20; G21; 330; Monetary Policy; Bank Stability; Credit